APPLICATION OF ADJUVANT ASSOCIATED WITH FUNGICIDE TO CONTROL THE TARGET BLACK (Corynespora cassiicola) IN SOYBEAN CULTURE - de Vietro Filho, Sergio; Hashimoto Fengler, Felipe (Journal of Interdisciplinary Debates, 2022)
Soybean represents one of the main agricultural assets in Brazil. However, due to the climatic conditions of high temperature and humidity, it is subject to fungal diseases, which can compromise the productivity and efficiency of the agricultural system. This work evaluated the efficiency of the mixture of SERE 7 adjuvant with fungicide to combat the target spot in soybean. The application was carried out 14 days after the R1 stage and 34 days after the R1 stage, compared to application of the fungicide alone. The results showed that there were no significant differences in the phenological stages: plant height, height of insertion of the first pod and plant population; however, a lower target spot severity was observed, with less defoliation and an increase of 8.3% (5.0 sc ha⁻¹) in terms of productivity. The association of SERE 7 proved to be beneficial, enhancing the action of the fungicide in combating the target spot in the soybean crop.